(untitled) (Gland, Switzland, 1990)
There is today a growing awareness that many wetlands are more valuable in their natural, or only slightly modified state, than if drained, dyked or built upon. Past neglect of wetlands has meant that there is insufficient material available on policy guidance, planning techniques, or management methodologies for their conservation and sustainable use in different regions This publication begins to redress the balance by reviewing the importance of wetlands, examining the reasons for wetland loss, and identifying ways and means to improve wetland management.
Keywords: Bảo tồn môi trường thiên nhiên Wetland,Wetland conservation